Negotiating Qur’anic Teachings and Local Beliefs: Muslim Community Perceptions of Magic in North Luwu, Indonesia - Muhammad Zuhri Abu Nawas; Ika Nur Wahyuni (Postgraduate Program of the State Islamic Institute of Palopo, 2023)
Belief in magic (sihr) continues to persist within many Muslim communities despite the explicit prohibition of harmful magical practices in Islamic teachings. This study investigates how Muslims in Banyuwangi Village, North Luwu Regency, Indonesia, perceive magic and negotiate Qur’anic teachings with local cultural beliefs. Employing a qualitative field research design, data were collected through observation, semi-structured interviews, and documentation involving religious leaders, community leaders, and local residents. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that community understandings of magic are shaped by both Islamic teachings and inherited local traditions. Participants generally acknowledge the existence of magic as described in the Qur’an, particularly through narratives concerning Harut and Marut, the magicians of Pharaoh, and verses of spiritual protection. At the same time, local cultural beliefs continue to influence interpretations of supernatural phenomena and magical practices. The study identified six forms of magic commonly recognized within the community: separation magic, love magic, madness-inducing magic, marriage-blocking magic, santet, and pesugihan. These forms are associated with social relationships, economic aspirations, personal conflicts, and spiritual concerns. The findings further demonstrate that community members distinguish between harmful magical practices and spiritual practices perceived as legitimate forms of protection and healing. This study argues that perceptions of magic among Muslims in North Luwu reflect an ongoing negotiation between Qur’anic doctrine and local cultural traditions, illustrating the dynamic interaction between scriptural authority, lived religion, and cultural experience in contemporary Muslim society